Customized Approach to the Implementation of Educational Programs for Training Engineers - N. A. Antonenko; T. A. Asaeva; O. V. Tikhonova; N. V. Grechushkina (Высшее образование в России, 2020)
The article discusses peculiarities of the customized approach, which takes into account the requirements of specific employers to the process and content of specialists’ training. Since the final consumer of the educational service provided by tertiary educational organization is the employer who hired the graduate, it is necessary to focus on the specifics of a particular organization activity when training specialists. Customized training is based on the collaboration of the University and the partner organization-employer, which consists in coordinating and adjusting educational programs within the existing standards to form professionally significant skills of graduates demanded by the employer, and involves further employment of the graduate in this organization. In this case, the specified organization acts as an investor or co-investor in the training of a future specialist. The employer’s participation in the educational process includes cooperation with the university not only in development of curricula and work programs of disciplines, but also in organization of seminars, conferences, in providing platforms and equipment for students to have their practice and to do their projects in real production conditions while solving actual professional problems. Customized training is one of the mechanisms to solve the problem of overabundance of specialists in some industries and a shortage of highly qualified personnel in others.